Telemedicine technologies : information technologies in medicine and digital health - Fong, Bernard; Fong, A. C. M.; Li, C. K. (Chi Kwong), 1952- (Hoboken : Wiley, 2020)
"Since the launch of Telemedicine Technologies (Wiley, 2010), the technologies surrounding telemedicine have changed immeasurably, particularly with the emerging trends of Internet-of-Things (IoT), digital/e-Health, and wearable, smart and assistive technologies. This second edition overhauls and expands on the original text to reflect the technical advances of the last decade. It covers applications from traditional healthcare services to remote patient monitoring and recovery, to alternative medicine and general health assessment for maintaining optimal health. This welcome update brings together a broad range of topics demonstrating how information and wireless technologies can be used in healthcare"--
Communication networks and services -- Information and communications technology in health monitoring -- Data analytics and medical information processing -- Telemedicine system deployment -- Safeguarding medical data and privacy -- Information technology in alternative medicine -- Telecare -- Wearable healthcare -- Smart and assistive technologies -- Future trends in healthcare technology
BIBINDX
Keywords: Telecommunication in medicine; Telemedicine -- methods; Telemedicine -- instrumentation; Medical Informatics Applications; Wearable Electronic Devices; Electronic books